2017
DOI: 10.1038/s41598-017-11094-3
|View full text |Cite
|
Sign up to set email alerts
|

CG200745, an HDAC inhibitor, induces anti-tumour effects in cholangiocarcinoma cell lines via miRNAs targeting the Hippo pathway

Abstract: Cholangiocarcinoma is a devastating malignancy with fatal complications that exhibits low response and resistance to chemotherapy. Here, we evaluated the anticancer effects of CG200745, a novel histone deacetylase inhibitor, either alone or in combination with standard chemotherapy drugs in cholangiocarcinoma cells. CG200745 dose-dependently reduced the viability of cholangiocarcinoma cells in vitro and decreased tumour volume and weight in a xenograft model. Administering CG200745 along with other chemotherap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
47
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 51 publications
(52 citation statements)
references
References 49 publications
(51 reference statements)
2
47
0
Order By: Relevance
“…These contradictory effects might reflect the distinct roles of individual HDACs in the immune responses. Therefore, the novel discovery of CG-745 in anti-cancer immunity suggests an excellent combination partner of various cancer immunotherapy and supports the reason why CG-745 shows the excellent synergistic efficacy in the combination treatment of various mouse tumor models such as in cholangiocarcinoma, pancreatic cancer, prostate cancer, and non-small cell lung cancer [30][31][32][33].…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…These contradictory effects might reflect the distinct roles of individual HDACs in the immune responses. Therefore, the novel discovery of CG-745 in anti-cancer immunity suggests an excellent combination partner of various cancer immunotherapy and supports the reason why CG-745 shows the excellent synergistic efficacy in the combination treatment of various mouse tumor models such as in cholangiocarcinoma, pancreatic cancer, prostate cancer, and non-small cell lung cancer [30][31][32][33].…”
Section: Discussionmentioning
confidence: 71%
“…While HDACis in anti-cancer therapy are commonly known as apoptosis inducers through anti-cancer gene expression and cell cycle arrest, recent studies have shown anti-tumor efficacy of HDACis in certain cancer types [26][27][28][29]. CG-745 is a HDAC inhibitor, and it has been reported as a potent anti-cancer agent in cholangiocarcinoma, pancreatic cancer, prostate cancer, and non-small cell lung cancer [30][31][32][33]. In cholangiocarcinoma, CG-745 is known to target the Hippo pathway via upregulation of miR-509-3p expression [33].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We presume that CG200745 may not cause renal insufficiency because CG200745 works by inhibiting over-production of angiotensinogen or Ang II in response to HFD not by random inhibition of existing angiotensinogen or Ang II. Of course the side effects of CG200745 should be studied thoroughly but good thing is that the dose we used in this study (200 μg/ kg) is greatly lower than the dose of clinical trial (1.275-6.25 mg/kg) (Kim et al 2015) or other researches at 5 mg/kg (Lee et al 2016;Bae et al 2019) or 35-45 mg/kg (Hwang et al 2012;Jung et al 2017) reducing the possibility of side effects. In this study, even combined with HFD, 200 μg/kg i.p.…”
Section: Discussionmentioning
confidence: 98%
“…Still, we acknowledge that detection methodologies (microarrays with detection of biotin labeled ncRNAs versus TaqMan assays involving detection of PCR products after cleavage of quenching hybridizing probes) and quantification analyses (eg, different types of sample normalization, software, and thresholds) could have an influence on the results. However, several papers show that in general there is a very good concurrence in studies where miRNA levels was measured by both GeneChip miRNA 4.0 Array and TaqMan PCR analysis …”
Section: Discussionmentioning
confidence: 99%